Fungsi Tari Mantang Balam di Kabupaten PALI Provinsi Sumatera Selatan - Cyintia Deby Arianti; Dessy Wardiah; Nugroho Notosutanto Arhon Dhony (SENDRATASIK UNP, 2023)
This study aims to describe the function of dance in PALI District, South Sumatra. In this research, it is a qualitative descriptive research. The object of research is the Mantang Balam dance. The data source for this research is informants, namely people who have knowledge about the Mantang Balam dance (choreographers, dancers, and Head of the Culture and Tourism Office of PALI Regency). Data collection techniques are carried out by observation, interviews, and documentation. The research instrument was the researcher himself with the aid of interview notes and a camera. Data analysis was carried out in a qualitative descriptive manner with observation, interviews and documentation. Checking the validity of the data using triangulation techniques. The results of the study are as follows: 1) the function of dance is as a guest welcoming ceremony, in this function dance is performed to welcome guests. 2) Function as entertainment, namely the Mantang Balam dance performed at circumcisions, wedding receptions and Regency Anniversary. 3) The function of dance as a spectacle/performance, namely the Mantang Balam dance is shown at art performances or dance festivals. 4) The function as an educational medium, in that function, the Mantang Balam dance is a medium for educating students in learning.